Memutus Rantai Domestic Violence Melalui Kesetaraan Gender dalam Hukum Keluarga Islam - Laila Puspita Anggraeni; Syahidin Syahidin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The massive patriarchal culture in society, misunderstanding of religion and unequal power in the family have resulted in high rates of domestic violence in Indonesia, where women are often the victims of violence. This violence often leads to divorce, while the wife is always the loser. This article discusses the importance of gender equality in Islamic family law as an effort to break the chain of domestic violence and achieve the goal of a harmonious marriage. This article uses the library research method by collecting literature related to domestic violence and family law in Indonesia. The analysis is conducted using the normative-inductive method with a gender justice approach, focusing on the position of men and women in the marriage relationship. In the discussion, this article reviews domestic violence, the forms of violence that occur, as well as the causes of domestic violence elaboration of family regulations in Muslim countries. Efforts to eliminate domestic violence and create harmonious families require the implementation of gender equality in family law. This is key to ensuring the well-being and protection of all family members, as well as to achieving the essence of the purpose of marriage in Islam.